Óbitos por suicídio no maranhão: tendência, fatores associados e distribuição espacial - SILVA, Robson Mariano Oliveira (2023)
Suicide is a complex and multidetermined phenomenon, and it is a worldwide public health problem. Brazil is among the ten leading countries in absolute numbers of suicides, and the Northeast region stands out in the increase of self-induced death rates in recent years. However, facing suicide has obstacles that hinder awareness, prevention, and data collection on the subject, and it is important to conduct epidemiological studies to predict scenarios and the possible factors that alter its behavior, making it possible to understand the vulnerability of population groups and provide relevant information for surveillance. Therefore, this study aimed to analyze the epidemiological, spatial and temporal aspects of deaths by suicide in Maranhão from 2011 to 2021. This is an ecological study of time series, with distinct measures of analysis. Data on deaths by suicide were collected from the Mortality Information System of Maranhão from January 1, 2010 to December 31, 2021. Descriptive statistics of the epidemiological context variables were performed and to evaluate the association between epidemiological characteristics of suicide and the outcome death, simple and multiple logistic regression models were used, and odds ratios were expressed. Annual mortality rates for the period were calculated by regional health units (RHU). The mortality trend analysis was processed using Prais-Winsten regressions. These analyses were performed via SPSS 24.0 software. To spatially distribute mortality rates, spatial area analysis was performed and spatial autocorrelation analysis was performed using the Global and Local Moran Index (LISA) via GeoDa software version 3.16.2, grouped into quadrennials: 2010-2013, 2014-2017, 2018-2021. The thematic maps were elaborated in QGIS 3.22.7. The research was approved by the Ethics Committee on Research involving Human Beings of the Federal University of Maranhão (UFMA) with opinion no. 5.384.011. A total of 3452 deaths by suicide were reported. Of these, the municipalities of São Luís and Imperatriz had the highest number of notifications (437 and 182, respectively). The majority of deaths were male (81.1%), between 20 and 29 years old (27.1%), mixed race (73.1%), without partner (64.9%), with schooling from 4 to 7 years (31.8%), and occurrence at home (59%). Suicide mortality rates ranged from 3.3 occurrences per 100,000 inhabitants in 2010, to 5.3 occurrences in 2021, showing an increasing trend over the years. The age groups 20 to 29 years and ≥ 40 to 49 years, being indigenous, having higher education < 4 years and predominance of death in the household were risk factors for deaths by suicide in this study. The spatial distribution of the rates allowed the identification of municipalities with high rates of occurrences in the analyzed trienniums, and the spatial pattern located in the southern portion of Maranhão. The Global Moran analysis indicated systematic positive autocorrelation, and in the Local Moran analysis significant clusters were identified. These findings raise the need for public policies that intensify the strategies for monitoring and preventing suicide, strengthening programs within the state, in addition to the provision of permanent training for professionals involved in care management.